Load estimation and vibration monitoring of scale model wind turbine blades through optical fiber sensors. (4th June 2021) - Cazzulani, Gabriele; Cinquemani, Simone; Benedetti, Lorenzo; Belloli, Marco
Abstract: Experimental activities on wind turbine models allow to speed up their design as well as the development of robust and effective control algorithms. Intending to have large information on load distribution on the blades, this work presents an experimental setup of a model wind turbine blade instrumented with two different types of optical fiber sensors (FOS). The first one is a traditional chain of Fiber Bragg Grating sensors, able to measure a large number of strain values; the second is based on Optical Backscatter Reflectometry (OBR), able to provide a continuous strain measurement. The experimental setup is calibrated to estimate load distribution along the blade and the two technologies are compared. The results of the experimental campaign suggest that optical fiber sensors could represent an interesting solution for real-time continuous load monitoring purposes.